Improving and Maximizing the Financial Performance of MSMEs: A Case Study on MSMEs in the Bangka Belitung Islands Province - Christine, Christine; Zukhri, Nizwan; Saputra, Darman (Journal of Management Economic and Financial, 2024)
Even in times of financial crisis, MSMEs remain an important economic tool that influence Indonesia's economic growth. MSMEs have the power to raise people's standard of living, particularly in terms of money. The purpose of this study is to investigate how the financial performance of MSMEs in the Bangka Belitung Islands Province is impacted by credit giving, financial inclusion, fintech, and intellectual capital characteristics. This study uses an associative methodology and is quantitative in nature. Purposive sampling procedures were used to obtain 102 MSME actors for the sample. SPSS software version 26 is used to assist with the data analysis technique. The study's findings demonstrate that financial inclusion (X2), fintech (X5), intellectual capital (X6), and partial credit giving (X1) all significantly and favorably impact MSMEs' financial performance. The Bangka Belitung Islands' MSMEs' financial performance is positively and significantly impacted by the concurrent factors of credit granting, financial inclusion, fintech, and intellectual capital. The independent variable accounts for 88.5% of the variation in the dependent variable, with the remaining 11.5% being impacted by factors not examined in this study, according to the R Square value of 0.885 in this investigation.